Påverkan av jakt och katastrofer på lodjursstammen (Lynx lynx) i Sverige: En sårbarhetsanalys - Dahlberg, Julia (Karlstads universitet, Fakulteten för hälsa, natur- och teknikvetenskap (from 2013), 2024)
The eurasian lynx (Lynx lynx) has a wide distribution and occurs in the palearctic region. In Europe, the lynx has been persecuted and exterminated from several of its natural distribution areas and has also been subject to persecution in Sweden, where a high hunting pressure led to a reduced population that almost went extinct. Today, the Swedish lynx population has recovered but is kept down by licensed hunting, which is strictly controlled due to the lynx's protection status. However, Sweden's government has backed a proposal for reduced protection that could potentially lead to higher hunting quotas and thus threaten the lynx's future, because of predators’ vulnerability to high hunting pressures and smaller populations’ vulnerability to stochastic events such as catastrophes. The purpose of this study was to investigate the development of the Swedish lynx population and how high the risk of extinction is now, with increased hunting quotas and if catastrophes would occur both with current hunting quotas and increased hunting quotas. Based on the purpose, the questions that were answered were the following: 1) What does the population development and extinction risk look like for the Swedish lynx population in the next 100 years with current hunting quotas? 2) How do higher hunting quotas affect the Swedish lynx population development and extinction risk in the next 100 years? 3) How would catastrophes with current hunting quotas and increased hunting quotas affect the Swedish lynx population development and extinction risk in the next 100 years? The questions were answered through a population viability analysis performed in Vortex 10 where four scenarios were created. In scenario 1, the null scenario, the Swedish lynx population development and extinction risk over 100 years were investigated in relation to current hunting quotas. In scenario 2, the Swedish lynx population development and extinction risk over 100 years were investigated in relation to current hunting quotas and catastrophes. In scenario 3, ...